Prolonged Voluntary Running Negatively Affects Survival and Disease Prognosis of Male SOD1G93A Low-Copy Transgenic Mice - Garbugino, Luciana; Golini, Elisabetta; Giuliani, Alessandro; Mandillo, Silvia (Frontiers in Behavioral Neuroscience, 2018)
Amyotrophic Lateral Sclerosis (ALS) is a disease in which physical activity plays a controversial role. Epidemiological studies indicate an association between intense exercise and risk of developing ALS. To study the impact of physical activity on ALS, mouse models rely mostly on forced exercise. In this study we hypothesized that voluntary wheel running could represent a better model of the influence of exercise in the pathogenesis of ALS. We used an automated home-cage running-wheel system that enables individual monitoring of performance. To verify the effect of voluntary running on disease progression, prognosis and survival as well as motor functions, we challenged SOD1G93A low-copy male and female mice on one (1 RW, at age 24 weeks) or multiple (3 RW) running sessions at age 13, 18 and 24 weeks. In parallel we measured performance on Rotarod and Grip strength tests at different ages. Several parameters were analyzed through Principal Component Analysis in order to detect what indices correlate and may be useful for deeper understanding of the relation between exercise and disease development. We found mutant male mice more negatively affected than females by prolonged and repeated exercise. SOD1G93A low-copy male mice showed shorter survival, increased body weight loss and poorer disease prognosis when exposed to multiple running sessions. These findings could encourage the investigation of the pathogenetic mechanisms underlying the supposedly increased risk to develop ALS in humans engaged in specific and intense exercise activities.